TRANSMISSION GEAR IN CALCULATIONS MOTORCYCLE SHOP FOR SPEED (DEALER) OFFICIAL - Nugroho Purnomo; Susi Wagiyati, SKom, MM (Jurnal Sistem Informasi, 2001)
Transmission gear is part of the driving of a motor vehicle. If there is no vehicletransmission gear can not move properly. To calculate the velocity of each tooth isstill in manual and mekaniklah only knows.Computerized calculation of transmission gear can make the rider to be able to knowthe maximum speed is generated each sustu vehicle transmission gear, also can giveaccurate information.